Early transcriptome responses of the bovine midcycle corpus luteum to prostaglandin F2α includes cytokine signaling. (5th September 2017) - Talbott, Heather; Hou, Xiaoying; Qiu, Fang; Zhang, Pan; Guda, Chittibabu; Yu, Fang; Cushman, Robert A.; Wood, Jennifer R.; Wang, Cheng; Cupp, Andrea S.; Davis, John S.
Abstract: In ruminants, prostaglandin F2alpha (PGF2α)-mediated luteolysis is essential prior to estrous cycle resumption, and is a target for improving fertility. To deduce early PGF2α-provoked changes in the corpus luteum a short time-course (0.5–4 h) was performed on cows at midcycle. A microarray-determined transcriptome was established and examined by bioinformatic pathway analysis. Classic PGF2α effects were evident by changes in early response genes (FOS, JUN, ATF3) and prediction of active pathways (PKC, MAPK). Several cytokine transcripts were elevated and NF-κB and STAT activation were predicted by pathway analysis. Self-organizing map analysis grouped differentially expressed transcripts into ten mRNA expression patterns indicative of temporal signaling cascades. Comparison with two analogous datasets revealed a conserved group of 124 transcripts similarly altered by PGF2α treatment, which both, directly and indirectly, indicated cytokine activation. Elevated levels of cytokine transcripts after PGF2α and predicted activation of cytokine pathways implicate inflammatory reactions early in PGF2α-mediated luteolysis. Graphical abstract: Highlights: Analysis of the bovine luteal transcriptome at 0.5–4 h post-PGF2α treatment. Transcriptomics and bioinformatics predict classical PGF2α and cytokine signaling. Reduced cholesterol availability may contribute to early decreases in progesterone. PGF2α rapidly changes cytokine and cytokine targets expression at < 4 h. Reduced progesterone and increased cytokine signals may prime the CL for luteolysis.